Scopophilic objectification and the digital afterlife of women’s live streams on YouTube in Indonesia - Arif Zuhdi Winarto; Faruk Faruk; Suzie Handajani (Center for Sociological Studies and Community Developmen, 2026)
This study examines how women's live videos are repurposed into repeatable objects of scopophilic consumption through re-editing practices on a popular Indonesian YouTube channel. Focusing on @sebo*channel, the study analyzes how live content originally intended for self-presentation or interaction is extracted, re-arranged, and circulated into new visual forms that intensify the logic of the male gaze, voyeuristic pleasure, and objectification. Using netnography and qualitative visual content analysis, the study uses selected videos and public comments to examine how framing, camera angles, slow motion, zoom, and compilation editing reshape women's bodies and gestures into visual spectacle. The analysis shows that objectification is produced not only by visual editing, but also through the interplay between platform features and audience participation. Commentary practices such as greetings, compliments, erotic comments, moral policing, and gesture requests extend the objectifying gaze beyond the video itself and help normalize patriarchal spectatorship. The study also suggests that modest dress, religious expression, and moral language do not necessarily interfere with scopophilic pleasure. Instead, they may coexist and even support it in the Indonesian digital context. The @sebo*channel account, through YouTube, actively reconfigures visibility, circulation, and value, transforming women's live broadcasts into a digital afterlife of commercialized spectacle.